1999
DOI: 10.1007/s002469900446
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Echocardiography with Extended Transesophageal Atrial Pacing: Predicting the Efficacy of Permanent Atrial Pacing in the Patient with a Small Left Ventricle and Sinus Node Dysfunction

Abstract: A 2100-g neonate underwent a two-ventricular surgical repair of a right ventricle-dominant unbalanced atrioventricular septal defect associated with the heterotaxy syndrome and sinus node dysfunction. Postoperative congestive heart failure persisted despite bradycardia management by temporary ventricular pacing. Spectral Doppler echocardiographic analysis of pulmonary venous inflow and aortic outflow patterns demonstrated significant improvement with transesophageal atrial pacing. Extended transesophageal paci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also, our case duration of 3.5 hours could be used in future as a base reference for continuous transesophageal pacing in very-lowbirth-weight infants. Previous case reports have only described low-birth-weight infants 5,10 and these two case reports were large discrepancies in the pacing time. One is between short duration during surgery 5 and the other is 2 days.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Also, our case duration of 3.5 hours could be used in future as a base reference for continuous transesophageal pacing in very-lowbirth-weight infants. Previous case reports have only described low-birth-weight infants 5,10 and these two case reports were large discrepancies in the pacing time. One is between short duration during surgery 5 and the other is 2 days.…”
Section: Discussionmentioning
confidence: 90%
“…One is between short duration during surgery 5 and the other is 2 days. 10 The safe pacing duration is not established in low-birth-weight infants, to say nothing of very-low-birth-weight infants. Although a previous case series study existed only in dogs, which described experimentation in 55 dogs, 9 it showed that more than 4 hours of pacing time increases the risk of oesophageal burn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation